Complication rates among women undergoing preventive mastectomy: An Austrian registry. Issue 9 (25th May 2020) - Leser, Carmen; Deutschmann, Christine; Dorffner, Georg; Gschwantler‐Kaulich, Daphne; Castillo, Deirdre Maria; Abayev, Sara; Stübler, Madeleine; Reitsamer, Roland; Singer, Christian
Abstract: Germline variations in the BRCA‐1 and BRCA‐2 genes are associated with an increased risk of breast cancer. These variants are found in 5% of all breast cancer cases. Prophylactic mastectomy is the most effective risk‐reducing method and shows high rates of patient satisfaction and acceptance. We established a registry of Austrian BRCA‐1 and BRCA‐2 mutation carriers who had undergone mastectomy for oncologic or prophylactic reasons. Data were collected on the type of operation, complications, and type of reconstructive surgery for patients between 2014 and 2017. The complication rate in patients with nipple‐sparing mastectomy was significantly lower (23.1%) than in those with other types of mastectomies (60.7%; P  = .005). In patients with implant‐based breast reconstruction, subpectoral placement was associated with a significantly higher rate of complications than prepectoral placement ( P  = .025). Median implant volume was 350 cc (range: 155‐650 cc), and a 100‐cc increase was associated with doubling of the odds of a complication (regression coefficient = 0.007); based on this finding, some surgeons may decide on using smaller implants. In summary, we identified significant associations between the risk of complications and surgical characteristics, and found host factors like diabetes, BMI, and smoking among Austrian patients with BRCA‐1 and BRCA‐2 variants.